Pesticide-Organism Interactions - Frederick M. Fishel (EDIS)
This guide addresses the various responses of living organisms to pesticides. This document is PI-43, one of a series of the Pesticide Information Office, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date June 2005.